Pengaruh Fintech Terhadap Inklusi Keuangan : Tinjauan Sistematis - Benediktus Rolando (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2024)
Financial technology (fintech) has emerged as a transformative approach to addressing systemic barriers in financial access, particularly for underserved and marginalized populations traditionally excluded from conventional financial services. This systematic literature review employs a qualitative methodology utilizing systematic literature review (SLR) techniques, following the PRISMA guidelines through comprehensive database searches across Scopus and Google Scholar, systematically screening peer-reviewed articles published between 2019-2024, with inclusion criteria focused on studies directly addressing fintech's impact on financial inclusion. The success of fintech-driven financial inclusion strategies critically depends on developing inclusive technological ecosystems, creating supportive regulatory frameworks, prioritizing consumer protection, and fostering collaborative partnerships between policymakers, financial institutions, and technological innovators. Ultimately, this research underscores the transformative potential of financial technology in democratizing financial access, while highlighting the complex, multidimensional challenges requiring continued research, innovation, and collaborative approaches to truly advance global financial inclusion.